‘Sora is incredible and scary’: public perceptions and governance challenges of text-to-video generative AI models - Kyrie Zhixuan Zhou; Abhinav Choudhry; Ece Gumusel; Madelyn Rose Sanfilippo (Information Research: An International Electronic Journal)
Introduction. Text-to-video generative AI models such as Sora OpenAI have the potential to disrupt multiple industries. In this paper, we report a qualitative social media analysis aiming to uncover people’s perceived impact of and concerns about Sora’s integration.